THE INFLUENCE OF AUTHORITARY PARENTING STYLES IN THE FAMILY ON THE SPEAKING ABILITY OF EARLY CHILDREN IN PAUD IN CIREUNGHAS DISTRICT - Lia Shofia; Elnawati; Redi Awal Maulana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Language development, particularly vocabulary mastery and speaking skills, is an important aspect of early childhood growth and development. One factor influencing a child's language development is the parenting style applied within the family. This study aims to determine the speaking skills of early childhood and analyze the influence of authoritarian parenting styles in families on the development of vocabulary and speaking skills of early childhood in early childhood education (PAUD) in Cireunghas District. This study used a quantitative approach with a survey method. The study population was 1,311 parents of early childhood children (4-6 years old) attending PAUD/TK in Cireunghas District, with a sample of 78 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using prerequisite tests and simple linear regression analysis. The results showed that the data were normally distributed and the relationship between variables was linear. The results of the simple linear regression test indicated that authoritarian parenting styles significantly influenced the development of vocabulary and speaking skills of early childhood. This finding suggests that the higher the implementation of authoritarian parenting styles in the family, the greater the potential for inhibiting the development of vocabulary and speaking skills of children. Therefore, a more communicative and dialogical parenting pattern needs to be developed by parents to optimally support the language development of early childhood.